Towards an understanding of corporate social responsibility a case study of the Eden Summer Enrichment Program (ESEP) of Eden Nature Park (ENP) - Galenzoga, Mary Grace E.
This is a case study of exploring the Corporate Social Responsibility concept of Eden Nature Park in relation to its Eden Summer Enrichment Program which is in partnership with Kauswagan Foundation. The study aimed to describe the concept of CSR of Eden Nature Park (ENP), the nature of Eden Summer enrichment Program (ESEP), and the perception of its beneficiaries pertinent to ENP after conducting ESEP. Though these descriptions the study answered the question on whether business should involve itself in CSR in the context of a resort and nature park. The respondents for this study are the special assistant to the Chairman of ENP and at the same time, the program coordinator of ESEP, Ms. Vida Maya Ko, and the 5 high school students who were the program's beneficiaries. The interview with the company representative consisted of questions that asked more of the views of the company towards CSR. The questions deal specifically on the company's CSR perception, conceptualization, objectives, implementation, and company's self-evaluation of ESEP. On the other hand, the individual perception of the beneficiaries towards ENP was also explored. The researcher asked the beneficiaries questions about their views towards the company and the effects of the program to their lives. Also, the established relationships between the beneficiaries and the company via beneficiaries' perceptions were solicited from them. Eden Nature Park at present lacks formality in their concept of CSR. The company receives CSR in its formal aspect, as a requirement, in which companies whose business pose risks of environment and societal problems are expected to comply. In their own case, the company employed projects that are described as somehow CSR in a discretionary and philanthropy and sponsorship as part of the owner's initiatives of helping its immediate community. The beneficiaries developed favorable impression towards the company through its projects. ESEP in particular had oriented them towards excellence, self-fulfillment and service. Also, the program developed good relationships between the company and its community. The program and the company can be identified as one by the beneficiaries, and their perceptions are over-all positive. ESEP became a source of innovation of the company since it suited the need of one of the company's multiple stakeholders ? the youth, who felt they were neglected by the company before. The program was also an opportunity for the company to utilize their resources as they pursue goodwill and projects for their community. Moreover, the program had increased the level of trust of the community towards the company, strengthened and created alliances, and generated new forms of learning for the company. ESEP can be a potential CSR project based on its creation, implementation, effects to its beneficiaries and benefits to the company. Based on the results of the study, the researcher can imply that adopting the concept of CSR based on the case of ENP's ESEP, is not an intrusion in the corporate affairs, but can be a way of attaining proven benefits and competitive advantage.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication